KATEKESE TENTANG PENGATURAN KEHAMILAN SECARA ALAMIAH - Gaudiawan, Antonius Virdei Eresto (CREDENDUM: Jurnal Pendidikan Agama, 2019)
The Catholic Church teaches that the end of human sexuality is toward unity and procreation. Therefore, on sexual morality the Catholic Church refuses artificial family planning but promotes natural family planning. The Catholic Church strongly proclaim this sexual morality. In fact, situation in the Christian families actually is not as good as the Church’s hope. It seem that s lot of Christian families disobey the Church’s teaching on sexual morality. Actually, most of Christian families know better and use artificial birth control. They think and feel that natural birth control is less safe and high risk. It happens because they only have a little and limited understanding on natural birth control. However, a complete understanding on natural family planning and a knowledge of negative effects of artificial birth control help Christian families to move toward natural birth control. Based on this awareness, the diocese of Surabaya, where this research is done, and catechists of family formation, need to evaluate seriously a premarital education class, especially in matter of time, method of catechesis, competence of catechists so that the premarital education class promote understanding of Christian families on natural family planning and it’s implementation